2010
DOI: 10.4103/0970-0218.74346
|View full text |Cite
|
Sign up to set email alerts
|

Study on obesity and Influence of dietary factors on the weight status of an adult population in Jamnagar city of Gujarat: A cross-sectional analytical study

Abstract: Background:Obesity has reached epidemic proportions globally and is a major contributor to the global burden of chronic diseases. Dietary factors are the major modifiable factors through which many of the external forces promoting weight gain act.Objectives:The objectives were to find the prevalence of overweight and obesity in the urban population of Jamnagar and to explore the effect of dietary factors on the weight status of the people.Materials and Methods:A cross-sectional study was conducted among the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
1
15
0
7
Order By: Relevance
“…The prevalence of overweight in an urban population of India, as found in National Family Health Survey during 2005-2006, was 11.38%. [9,10] The prevalence of obesity was 2.24% in the same survey. Though the prevalence found in the present study is higher than the national average, it is lower than that of developed countries.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of overweight in an urban population of India, as found in National Family Health Survey during 2005-2006, was 11.38%. [9,10] The prevalence of obesity was 2.24% in the same survey. Though the prevalence found in the present study is higher than the national average, it is lower than that of developed countries.…”
Section: Discussionmentioning
confidence: 98%
“…It was highest in the age group of 50-60 years. 21 From the above studies it is seen that there is association between age and development of obesity. It is also found that the development of obesity is more in females than males and there is association between gender and overweight/obesity and Sen et al also found that the prevalence of obesity was significantly associated with respect to sex.…”
Section: Age In Completed Yearsmentioning
confidence: 99%
“…11 And also with a study on obesity and influence of dietary factors on the weight status of adult population in Jamnagar city of Gujarat which showed that the prevalence of overweight and obesity in the urban population was found to be 22.04% and 5.20% respectively. 12 Our study showed that, obesity and overweight was more common in age group 38-47 and 48-57 years. Bulk of obesity i.e.…”
Section: Discussionmentioning
confidence: 76%
“…These figures had resemblance with one study conducted on adult population in Jamnagar city of Gujarat which showed that the prevalence of obesity rose with an increase in age up to 60 years. 12 In our study obesity and overweight was more or less equally distributed in male and female. In all WHO regions women were more likely to be obese than men and the prevalence is more in female than males similar to the present study but the association here is statistically not significant.…”
Section: Discussionmentioning
confidence: 85%